Endometriosis as an Infectious Disease: Association with Chronic Endometritis - Kotaro Kitaya; Takako Mihara; Masaya Mihara (Clinical and Experimental Obstetrics & Gynecology, 2023)
Objectives: Recent studies focus on immunological, infectious, and inflammatory aspects of endometriosis. Meanwhile, chronic endometritis (CE) is an immunological, infectious, and inflammatory disorder of the eutopic endometrium with unusual stromal plasmacyte infiltration. Mechanism: In this review article, we aimed to gain a better understanding of the relationships between endometriosis and CE. Findings in Brief: Accumulating evidence supports the idea that CE is associated with infertility of unknown etiology, repeated implantation failure in an in vitro fertilization-embryo transfer program, recurrent pregnancy loss, as well as several perinatal/neonatal complications. Endometrial biopsy/histopathologic examinations and/or hysteroscopy are required to make a definitive diagnosis of CE. Conclusions: While endometriosis has been long considered a cause of infertility, CE is also an emerging issue that may reduce fecundity in women of reproductive age. Endometriosis and CE share characteristics of endometrial proliferative nature. The potential relationships between these two diseases of the uterine lining warrant future studies.